Women's Domination in Their Relationship with Language in the Movie "Tilik The Series" - Kunti Zahrotun Alfi; Kastam Syamsi; Anwar Efendi; Hartono Hartono (Indonesian Journal of EFL and Linguistics, 2023)
This research aims to describe the dominance of women in the film "Tilik The Series" through dialogue and scenes using note-taking techniques. There were 8 episodes taken as research data. Through this technique, 9 dialogues related to female domination were obtained. The analysis was carried out using Sara Mills' critical discourse analysis. The research results show that in society, women occupy a position as subjects who can voice their opinions through loud speech and physical actions. This is done by the characters Bu Tejo to the parking attendant, Bu Tejo to Nopek, and Yu Ning to Pak Tejo. The actions taken by several figures encouraged village women to do the same. This shows that women have the power to influence other women. Furthermore, women who are abandoned by their husbands receive a low position and negative nicknames in society. The research findings from the film "Tilik: The Series" suggest a significant transformation in the roles and perceptions of women in society. Women are portrayed as subjects who are empowered, capable of leadership, and able to challenge traditional gender norms and stereotypes, while still respecting cultural traditions. This implies a move towards a more gender-inclusive and equitable society where women have a more significant voice and influence in both public and domestic spheres.